Respuesta :

5(3√x)+9(3√x)
=3√x(5+9)
=14(3√x)

answer is C. third choice 14(3√x)

Answer:

Option (c) is correct.

[tex]5(\sqrt[3]{x})+9(\sqrt[3]{x} )=14\sqrt[3]{x}[/tex]

Step-by-step explanation:

Given : expression [tex]5(\sqrt[3]{x})+9(\sqrt[3]{x} )[/tex]

We have to choose the correct option from the given options to the sum of the given expression.

Consider the given expression [tex]5(\sqrt[3]{x})+9(\sqrt[3]{x} )[/tex]

Taking [tex]\sqrt[3]{x}[/tex] common from both terms, we have,

[tex](\sqrt[3]{x})(5+9)=14\sqrt[3]{x}[/tex]

Thus, [tex]5(\sqrt[3]{x})+9(\sqrt[3]{x} )=14\sqrt[3]{x}[/tex]